Structure and Optical Properties of Titania-PDMS Hybrid Nanocomposites Prepared by In Situ Non-Aqueous Synthesis - Antoine R. M. Dalod; Ola G. Grendal; Anders B. Blichfeld; Vedran Furtula; Javier Pérez; Lars Henriksen; Tor Grande; Mari-Ann Einarsrud (Nanomaterials, 2017)
Organic-inorganic hybrid materials are attractive due to the combination of properties from the two distinct types of materials. In this work, transparent titania-polydimethylsiloxane hybrid materials with up to 15.5 vol. % TiO2 content were prepared by an in situ non-aqueous method using titanium (IV) isopropoxide and hydroxy-terminated polydimethylsiloxane as precursors. Spectroscopy (Fourier transform infrared, Raman, Ultraviolet-visible, ellipsometry) and small-angle X-ray scattering analysis allowed to describe in detail the structure and the optical properties of the nanocomposites. Titanium alkoxide was successfully used as a cross-linker and titania-like nanodomains with an average size of approximately 4 nm were shown to form during the process. The resulting hybrid nanocomposites exhibit high transparency and tunable refractive index from 1.42 up to 1.56, depending on the titania content.